Variantes do P21/WAF1 e da ciclina D1 e carcinoma de células escamosas de boca - Carolina Cavalieri Gomes (2007)
Genetic factors are known to be involved in oral squamous cell carcinoma (OSCC) development. We evaluated a possible association between CCND1 G870A and P21 C98A polymorphisms in OSCC, as well as the impact of the genotypes on protein immunoexpression. No statistical association between CCND1 and/or P21 genotypes in OSCC was demonstrated, although we found that people harboring the combined presence of at least one variant allele of both genes showed a 1.8 times more chance of developing OSCC compared to the referent genotype. OSCC tumours from individuals with P21 heterozygous genotype showed a significantly higher immunopositivity than tumours from wild-type individuals, demonstrating that P21 protein expression in OSCC is affected by P21/WAF1 genotype.